The missional role of the Holy Spirit: Ghanaian Pentecostals’ view and practice - White, Peter; Niemandt, Cornelius Johannes Petrus (Nelus) (2015)
This article discusses the missional role of the Holy Spirit from a Ghanaian Pentecostal’s perspective. In doing this, trinitarian mission is used as the point of departure and it was narrowed down to the missional role of the Holy Spirit. The Ghanaian Pentecostals’ view about the baptism and the infilling of the Holy Spirit as well as their practices concerning the subject are discussed. The article concludes that there is no way that the church could achieve her call without the role of the Holy Spirit, to convict sinners of their sin and also to empower the church to proclaim the gospel.
Free